Assessment of nutritional status and quality of life among patients with cancer who underwent major upper gastrointestinal system cancer surgery - Kaner, Gulsah; Yılmaz, Ahmet Zeki; Inanc, Neriman; Yıldırım, Merve Nur Sultan; Seremet Kurklu, Nilgun; Bellikci Koyu, Ezgi (Progress in Nutrition, 2018)
Aim: The risk of developing complications following major gastrointestinal system surgeries has risen in recent years despite of the development of methods and techniques for cancer surgery and increased preoperative care. Complications following surgical intervention reduce the quality of life of the patient, while increasing hospitalization time and mortality rates. In addition, surgery can lead to malnutrition in the postoperative period resulting from catabolism, which is caused by increasing the release of stress hormones and inflammatory mediators. This study was conducted to evaluate the nutritional status and quality of life and to determine the relationship between the two in patients with cancer who underwent major gastrointestinal surgery. Methods: Postoperative patients who underwent major upper gastrointestinal system cancer surgery by a general surgeon in the province of Kayseri, Turkey, aged between 20 and 80 years, and who met the criteria of the study, were included in the study. Socio-demographic characteristics, body composition, anthropometric measurements, and biochemical findings of the patients were recorded. NRS-2002 (Nutritional Risk Screening-2002) was used to evaluate the nutritional status of individuals and EORTC QLQ-C30 Version 3.0 (European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire) was used for the assessment of quality of life. Results: A total of 119 participants, 69 (58%) male and 50 (42%) female, participated in the research. The most common type of operation was partial/subtotal gastrectomy (41%). According to the NRS-2002 score, malnutrition risk was high in almost all males (98.6%) and females (88.0%), and nutritional support was necessary. It was determined that the albumin values ​​of the individuals who were at risk of malnutrition are lower, and their length of stay in the hospital was longer. When the EORTC QLQ-C30 scores of the individuals were evaluated, the general health status score average was 45.2 ± 18.20, the physical function score average was 67.3 ± 16.72, and the symptom score average was 36.1 ± 16.56 points. Symptom scores were found to be lower in women than men (p